Non‐metallic printed circuit board waste derived carbon for the supercapacitor electrode material. (4th March 2020) - Qin, Hengfei; Pan, Junli; Zhou, Yue; Zhu, Binglong; Huang, Jizhong; Huang, Hongying; Wang, Liangbiao; Hou, Yanbiao; Zhou, Quanfa
Abstract : Highly specific surface area carbon materials derived from the waste printed circuit board (WPCB) for supercapacitor electrode material are feasibly prepared via microwave carbonisation and KOH activation process with controlled activation temperature. The effect of activation temperature on the pore structure and the electrochemical performance of the products are studied. The results demonstrate that the appropriate pore structure plays an important role in the application of supercapacitor. The electrochemical performance tests show that the specific capacitance of WPCB‐800 can reach 134.2 F g −1 at current density of 200 mA g −1, and the capacity retention rate is 96.2% after 2000 cycles.